Opportunities For Cyber Notary Implementation In A Legal Perspective - Lili Julianti; Gunawan Djajaputra (Dinasti Research, 2024)
The capacity of notaries to provide top-notch services that are quick, strategic, and community-solving is crucial in this age of fast-paced technological, informational, and communicative advancements. The usage of a cyber notary is one strategy for delivering timely and strategic services to the public. To be clear, the power to certify electronically performed transactions is the only one that now exists under the umbrella of